Talking politics - Parekh, Bhikhu C.; Jahanbegloo, Ramin (Oxford : Oxford University Press, 2011)
Iranian scholar Ramin Jahanbegloo interviews one of the leading political thinkers our time, Bhikhu Parekh, and in the process addresses issues ranging from cultural diversity, religion, and global ethics to identity politics, liberal democracy, Islam and Europe, and Gandhi's role as a political thinker and social reformer.
Description based on print version record.
Keywords: Parekh, Bhikhu C. -- Political and social views; Parekh, Bhikhu C. -- Interviews; Gandhi, -- Mahatma, -- 1869-1948 -- Influence; India -- Politics and government -- 1977-; India -- Social conditions -- 1947-